Characterization of pathogenic endosymbionts in free-living amoebae isolated from indoor sport water complexes. - Haghbayan, Narjes; Niyyati, Maryam; Mahdavi, Fatemeh; Nemati, Sara; Mohebbi, Seyed Reza; Zabetpour Kurdi, Hannane; Pourhosseingholi, Mohammad Amin; Mirjalali, Hamed (International Journal of Environmental Health Research, 2026)
This study aimed to investigate FLA and their endosymbionts in indoor sport water complexes (ISWCs). A total of 90 samples were collected from 15 ISWCs. After morphological and molecular detection, fungi and viral pathogens were investigated in isolated FLA using real-time PCR. Totally, 51 (56.7%) were positive for FLA, including Acanthamoeba sp. Vermamoeba sp. Vahlkampfiidae, and Thecamoeba spp. in 33 (36.7%), 20 (22.2%), 24 (26.7%), and 2 (2.2%) of samples, respectively. The number of positive samples was 17 in each sauna biofilm, Jacuzzi, and pool water. The genotypes T4, T5, and T11 were characterized in Acanthamoeba sp.. All Vermamoeba spp. were V. vermiformis and all family Vahlkampfiidae were characterized as Naegleria sp.. Candida albicans and Aspergillus flavus were detected in two samples of pool water and Jacuzzi. The presence of AdV, NoV, and AsV was recorded in two Jacuzzi samples, in which AdV and NoV were detected in a sample at the same time. Our findings suggest that FLA can resist disinfectant used in ISWCs and high temperature of Jacuzzi. In addition, the presence of viral and fungal endosymbionts contributes to the important role of FLA in waterborne infections, particularly in places where people are in close contact with them.